The journey from student to paramedic in the UK ambulance service social and cultural issues in paramedic development - Donaghy, John (Paramedic); Waller, Diane, 1943- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
Drawing on extensive ethnographic research, this fascinating book highlights the challenges and contradictions faced by neophyte paramedics as they transition from a classroom setting into day-to-day clinical work placements. Shining a spotlight on the subculture of the UK Ambulance Service, as well as the paramedic profession more widely, it examines critically how language, cultural meanings, institutionalised rules, professional identity, and working practices determine key behaviours within paramedic practice, providing readers with insight into the profession not seen by members of the public or portrayed by media representations. The book draws on work of seminal authors and experts in the field to provide a sociological perspective on this not only challenging but also, at times, chaotic professional environment. Supported by fieldnotes as well as interviews with students and paramedics, the book will be essential reading for any student on the path to becoming a paramedic. It will also be valuable reading for those within the service who wish to better understand the hidden cultural and social components that lie beneath the practice itself.
Keywords: Great Britain. -- National Health Service; Allied health personnel -- Vocational guidance -- Great Britain; HEALTH & FITNESS / Health Care Issues; SOCIAL SCIENCE / Anthropology / Cultural